Optimization of Amaranthus production under irrigation and poultry manure application using grey relational analysis - Fasanu, Olugbenga; Oluwagbayide, Dare Samuel; Sosanya, Abolade Olayinka; Olorunwa, Omofunmi Eric (Journal of Agriculture Sustainability and Environment, 2024)
This study was carried out to optimize Amaranthus production under varying irrigation levels and poultry manure applications using Grey Relational Analysis. The experimental design was split-plot, where irrigation treatment was the main plot, while poultry manure was the subplot treatment. The irrigation levels are FIT50, FIT75, FIT100 and FIT135 which correspond to 50% Full irrigation, 75% full irrigation, 100% full irrigation and 135% full irrigation treatments, in combination with the poultry manure application rates M0t/ha, M5t/ha, M10t/ha and M20t/ha. Sixteen experimental treatments were arranged in a 4 x 4 factorial experimental design and replicated 3 times.  Sprinkler irrigation system was adopted for the study.  Results showed that there was corresponding increase in the response of Amaranthus growth characteristics and yield to the combination of irrigation and poultry manure treatments.  The Crop Water-use efficiency initially showed a linear corresponding increase to an average value of 473kg/ha/mm but later exhibits a diminishing return beyond FIT100 irrigation. While production cost showed continual increase to average value of $377/ha as the inputs treatment level also increased to FIT135 irrigation combined with the poultry manure M20t/ha. Grey Relational Grades (GRG) calculated were 0.854, 0.790, 0.787, 0.765, 0.740, 0.629, 0.621, 0.620, 0.546, 0.543, 0.515, 0.475, 0.458, 0.443, 0.417 and 0.403 respectively. Amaranthus cultivated under FIT100_M20t/ha treatment matched with the highest GRG value 0.854, making FIT100_M20t/ha treatment the optimum. Analysis of variance for the GRG showed that irrigation and poultry manure are highly significant input variables for Amaranthus production. The findings from this study guide farmers on the optimal combination of water and organic fertilizer to maximize Amaranthus yield and minimize resource waste, thereby enhancing sustainability in crop production.